Native Studies Keywords - Raheja, Michelle H.; Smith, Andrea, 1966-; Teves, Stephanie N. (Book collections on Project MUSE., 2015)
Publisher's description: This is an edited volume that provides definitions, meanings, and significances of select key concepts often used in Native studies. These concepts include: sovereignty, land, indigeneity, nations, blood, tradition, colonialism, and indigenous epistemologies/knowledges. The manuscript is divided into eight sections, and each section includes three or four essays about one of the concepts. The essays provide an historical, social, and political context for the concepts and indicate how they have been drawn upon by scholars of Native studies.